Initial validation of coaching behavior scales in volleyball - Jurko, D.; Tomljanovic, M.; Cular, D. (Sport Scientific and Practical Aspects - International Scientific Journal of Kinesiology, 2013)
The main goal of this research was to validate two measuring instruments for assessing coaching behavior in volleyball: Coaching Behavior Scale for Sport (CBS-S) and Leadership Scale for Sport (LSS). The research was conducted on a sample of 273 youth and junior male and female volleyball players. By validating the questionnaires of perceived coaching behavior it has been established that the reliability was good in all 7 scales of CBS-S, as well as in 3 out of 5 scales of the LLS questionnaire. The reliability was not satisfactory only in scales of autocratic behavior and positive feedback. The distribution shape and symmetry indicators indicate good sensitivity of all scales, and having the item selection performed in particular scales, all scales have good homogeneity. In the process of making the CBS-S questionnaire the views of top athletes and coaches were taken into consideration. It is why CBS-S can be recommended especially to those researchers willing to analyze the field of top sport. However, this research also proves that CBS-S can be used for assessing the behavior of coaches of young age groups